2021
DOI: 10.21203/rs.3.rs-676810/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Physicochemical Characterization of Cattle Dung Fibre Under the Hydrothermal Process

Abstract: Cattle dung fibre is a lignocellulosic material abundant and sustainable non-wood source of polymeric components, which can be converted into high added-value products. Hydrothermal treatment of the fibre obtained from cow dung was explored using four different temperatures (120, 140, 160 and 180 ◦C) and incubation times (0 and 120 minutes) at a fixed material to water ratio (1:10). The present study resulted in the highest yield of 94% (w/w) that gradually decreased with temperature and incubation time. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The comparison of the frass and the other fiber materials' chemical compositions is shown in Table 2 . The nonwood fibers ( Pennisetum alopecuroides 30 , cornstalk 31 , rice straw 32 and wheat straw 17 ) in Table 2 have been recorded in the application of pulping and cattle raising. According to the study's results, it was found that the holocellulose and α-cellulose content in the frass is higher, while the acid-insoluble lignin content is lower.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The comparison of the frass and the other fiber materials' chemical compositions is shown in Table 2 . The nonwood fibers ( Pennisetum alopecuroides 30 , cornstalk 31 , rice straw 32 and wheat straw 17 ) in Table 2 have been recorded in the application of pulping and cattle raising. According to the study's results, it was found that the holocellulose and α-cellulose content in the frass is higher, while the acid-insoluble lignin content is lower.…”
Section: Resultsmentioning
confidence: 99%
“…2 includes two variables. The digestion time (X 1 ) is set at a high level (+ 1) of 90 min and a low level (− 1) of 60 min, which is also set according to the traditional chemical pulping temperature 23 , while the NaOH dosage (X 2 ) is set at a high level (+ 1) of 14% and a low level (-1) of 0%, which the high level is set according to pulping conditions of Napier grass and the low level is set according to Fasake et al 17 . These conditions result in four factorial points, each representing one experiment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…in the pulp and papermaking industry. Furthermore, Fasake et al (2021) [17] subject the CDF to hot water treatment at temperatures ranging from 120°C to 180°C and analyze the yield, chemical compositions, and physical changes. The result indicates that hot water treatment can remove the lignin of CDF e ciently and degrade the hemicellulose, which causes the crack and pores structure exhibited on the CDF surface.…”
Section: Introductionmentioning
confidence: 99%